2021
DOI: 10.3389/fnagi.2021.749606
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Changes in Cortical Complexity in Right-Onset Versus Left-Onset Parkinson’s Disease in Early-Stage

Abstract: There is increasing evidence to show that motor symptom lateralization in Parkinson’s disease (PD) is linked to non-motor features, progression, and prognosis of the disease. However, few studies have reported the difference in cortical complexity between patients with left-onset of PD (LPD) and right-onset of PD (RPD). This study aimed to investigate the differences in the cortical complexity between early-stage LPD and RPD. High-resolution T1-weighted magnetic resonance images of the brain were acquired in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients (Shen & Xu, 2022). Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients (Shen & Xu, 2022). Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…This alteration in the cortical fractal structure may be an indirect consequence of damage sustained by the brain's subcortical regions. Previous studies noted altered cortical complexity in PD patients [36][37][38]. Clinically, the symptoms manifested by PD patients could be heterogeneous [3].…”
Section: Discussionmentioning
confidence: 93%
“…The study found widespread FD reductions in PD patients compared to HCs but no significant differences in GI. Zhang et al [37] studied differences in cortical complexity between early-stage right-onset and left-onset PD and HCs. They found that right-onset PD patients had decreased FD in the left superior temporal cortex compared to HCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients 24 . Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD 25 .…”
Section: Discussionmentioning
confidence: 95%